Exploring the Paradox of Natural Beauty and Management Neglect of Fodo Beach - Harefa, Afore Tahir; Gea, Juardiman Putra; Gea, Danieli; Gea, Irawan Jeprianus (Yayasan pendidikan dzurriyatul Quran, 2026)
Coastal tourism remains a primary driver of regional development, yet its sustainability is frequently compromised by the quality of local governance. Fodo Beach in Gunungsitoli presents a unique paradox where significant natural aesthetic capital is currently overshadowed by operational decline and infrastructure decay. This study aims to explore the disconnect between the destination’s natural potential and its management reality while identifying the specific factors contributing to its stagnation. Using a qualitative case study approach, data were gathered through in-depth interviews with family owners, visitors, and tourism officials, supplemented by field observations and thematic analysis. The findings reveal a